Biogenic Synthesis, Characterization, Along with Investigation of Cytotoxicity and Antibacterial Activities of Silver Nanoparticles Using Twigs of Polyalthia sclerophylla - Ismail bin Zainol (Tanjung Malim, 2024)
Biogenic Synthesis, Characterization, Along with Investigation of Cytotoxicity and Antibacterial Activities of Silver Nanoparticles Using Twigs of Polyalthia sclerophylla by Ismail bin Zainol